CARDIOLOGY: REALITY AND PROSPECTIVE. RESULTS OF RUSSIAN NATIONAL CONGRESS OF CARDIOLOGY - O. V. Gaysenok; A. S. Lishuta (Рациональная фармакотерапия в кардиологии)
Cardiology: reality and prospective. Results of Russian National congress of cardiology.